Recombinant fibromodulin has therapeutic effects on diabetic nephropathy by down-regulating transforming growth factor-β1 in streptozotocin-induced diabetic rat model - Maryam Foroutan Jazi (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s):Diabetic nephropathy is an important long-term complication of diabetes mellitus which appears to be partially mediated by an increase in secretion of transforming growth factor-β (TGF-β). Fibromodulin, the small leucine-rich proteoglycan, has been proposed to be the potent TGFβ1 modulator. In this study, the therapeutic effects of recombinant adenoviral vectors expressing fibromodulin on TGF-β1 expression on diabetic nephropathy were assessed. Materials and Methods:Forty-eight Sprague-Dawley rats were divided into 4 groups: STZ-induced diabetic rats (diabetic-control), fibromodulin adenovirus vector treated STZ rats (Ad- fibromodulin), and Ad-lacZ-treated STZ rats (Ad-lacZ), and vehicle control (PBS-control). At 10 weeks after STZ treatment, we measured urinary albumin excretion (UAE), urine creatinine was measured by Jaffe method.We also measured kidney TGF-β1 levels by reverse transcription polymerase chain reaction and Real-time PCR. Results:Urine  albumin to creatinine ratio or UAE level were listed in four groups. UAE difference between healthy and diabetic rats in all three groups were significant (P≤0.005) and between the control group and treated groups were not significant. Our results indicated that TGF-β1gene expression in diabetic rats were increased and difference between normal group and diabetic group were significant (P≤0.001). Fibromodulin gene transfection mediated by a recombinant adenovirus decreased TGF-β1 level in STZ-induced diabetic rats and TGF-β1 mRNA in diabetic kidney were reduced 2 weeks after                                   Ad-fibromodulin injection. Conclusion:Intraperitoneal injection of adenoviral vectors expressing fibromodulin  reduced TGF-β1 level in diabetic rat models. The molecular mechanisms involved in this process require further study.